Pengaruh Media Pembelajaran Website Terhadap Keterampilan Menulis Aksara Jawa Pada Siswa Kelas V - Adi Setiawan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe the differences in the application of website media to Javanese script writing skills in fifth grade students and the influence of website media on Javanese script writing skills in fifth grade students. This research method is an experimental type of non-equivalent control group design. Samples were taken by purposive sampling and obtained class VB as the experimental class and class VA as the control class. This study uses test data collection techniques, observations, questionnaires and documentation. Data analysis techniques used are Normality Test, Homogeneity Test, T-Test and Regression Test. The results of this study indicate that there are differences in the application of website media to Javanese script writing skills in fifth grade students, it can be seen that the probability value (sig.2-tailed) is 0.187. Because the probability value is greater than 0.05, the treatment of website learning media in the experimental group is more effective than the control group that is not treated or so that there is a significant difference in the post test, then Ha is accepted and there is an influence of website media on Javanese writing skills. This is evidenced by the pre-test and post-test significance of 0.004 < 0.005, which means the hypothesis is accepted. It can be concluded that there is a significant effect of using instructional media on students' writing skills.